HUMAN NATURE IN THE PERSPECTIVE OF ISLAMIC PHILOSOPHY - Yassir Lana Amrona; Umi Septina Anggraheni; Abid Nurhuda; Muhammad Al Fajri; Thariq Aziz (LP2M Universitas Ibrahimy, 2023)
As unique creatures, humans have specific characteristics that make them different from other creatures. It certainly makes scientists interested in studying it and including this theme in particular fields of study, including Islamic philosophy. Thus, this study aims to describe Human Nature from the Perspective of Islamic Philosophy. The method used is qualitative with literature study techniques, while the documentation model becomes a tool for data collection. Then, the essential and relevant things according to the theme are recorded, a careful analysis of the contents is carried out, and finally, it is concluded. The results of the study show that human nature in Islamic philosophy is placed as a creature that has a myriad of potentials with which he must maintain a relationship with the universe and its contents and continue to pay attention to ethical, moral, and social values to others to worship Allah so that he can achieve optimally the highest goal is to get a good life in the world and be safe in the afterlife.